Active Trading and (Poor) Performance : The Social Transmission Channel - Escobar, Laura (World Bank, Washington, DC, 2019)
Individuals often invest actively and generate inferior returns. Social interactions might exacerbate this tendency, but the causal effect from peer effects on active trading are difficult to identify empirically. This paper exploits the exogenous assignment of students to classrooms in a large-scale financial education initiative to evaluate the transmission of trading strategies among individual investors. The paper shows that favorable peer returns on single-stock transactions stimulate market entry among inexperienced investors, even when total portfolio performance among peers is negative. The results are consistent with selective communication: individuals with trading background share their most favorable trades, which attracts others to the stock market. Inexperienced individuals who are exposed to peers with large returns on single trades appear to overestimate the value of active trading. The paper finds that these rookie investors make more stock transactions, trade more speculatively, but also generate inferior returns. The findings show the strength of social communication as a key determinant of financial decision making.